The Stairway : in Art. (Rotterdam : Centrum Beeldende kunst, 1988)
Van den Akker, Elizabeth ; Janssen, Willem H. ; Trip, Franklin Julien ; Kapsenberg, Harry ; Montebasso ; Waakop Reijers, Dineke ; Waakop Reijers, Tom ; Yigitoglu, Esma
The Stairway in Art, Rotterdam, 1987.
boek
Keywords: Stairway